Distribuição espacial da lignina e do ângulo microfibrilar na parede celular de Eucalyptus grandis - Souza, Milene Teixeira de (2017)
The cell wall consists basically of lignin, cellulose and hemicelluloses, systematically organized in the primary and secondary walls, constituting the exoskeleton of the fibers. Cellulose microfibrils and lignin have a great influence on the physical and mechanical properties of the wood. In this context the aim of this work was to provide information on the natural variability of the microfibrils orientation through the secondary cell wall and to analyze the distribution of the lignin content in the fiber cell wall of normal, tension and opposite wood of Eucalyptus grandis. Two 28 year old Eucalyptus grandis trees were used, one with upright trunk and one with inclined trunk. Discs of 10 cm were removed at two heights, 1,30 m from the ground and 25% of the total height of the tree. Analyzes were performed for normal, tension and opposite wood. The determination of the mean microfibrillar angle (MFA) was made by polarized light microscopy and the angle of the cell wall layers by transmission electron microscopy. Lignin determination was performed by fluorescence and confocal microscopy, the quantification was realized using the software Image J. The mean MFA being the lowest in tension wood, with a value of 5,4°. A reduction of the microfibrillar angle in the pith to bark direction was observed. The layers S1, S2 and S3 and the transition between them were identified by the orientation of the cellulose microfibrils. The S2 layer presented lower AMF in relation to layers S1 and S3, with a decrease of the MFA from pith to bark. The MFA found in the tension wood for the S2 layer was close to the average angle of the cell wall. The tension wood showed lower fluorescence intensity.